PENDAPATAN DAN KETAHANAN PANGAN RUMAH TANGGA PETANI JAGUNG DI KECAMATAN BANDAR SRIBHAWONO KABUPATEN LAMPUNG TIMUR - Lutfia Khoirunnisa; Yaktiworo Indriani; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This study aimed to analyze income and the level of food security as well as the factors that influence the food security of household corn farmers. This research was conducted by a survey method in Bandar Agung Village and Sri Pendowo Village, Sub-district of Bandar Sribhawono, East Lampung Regency. Data collection was carried out in February to March 2018 which was analyzed by quantitative descriptive analysis and logistik ordinal statistical analysis. Samples of 69 household’s corn farmers were randomly selected by simple random sampling. The results of this study showed that cash income for corn farming per hectare in the first, secondand third planting season amounted to Rp12,872,858.32; Rp10,201,805.09 and Rp5,440,975.65. In average, household income of corn farmers in Sub-district of Bandar Sribhawono was Rp4,370,336.33. From the cross classification between energy suffeficiency and share of food expenditure which resulted four categories of corn farmers household’s food security,it showed that 7 households (10.14 %) were food resistant, 44 households (63.77 %) were less food, 5 households (7.25 %) were vulnerable to food and 13 households (18.84 %) were food insecure. The factors that influenced the level of food security of corn farmers in Bandar Sribhawono Sub-district were influenced by the food expenditure and household expenditure.Key words: corn farmers, food expenditure, food security, incom